Komunikasi Pemasaran Dalam Mempertahankan Daya Beli Konsumen Hallo Burjois - Sandi, Adelia Yuliani; Nursanti, Siti; Oxygentri, Oky (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2024)
The many coffee shops that have sprung up in the city of Karawang have a negative impact on the coffee shop owners themselves because they have created many competitors in the coffee shop world in Karawang. Therefore, every coffee shop must have a strategy to maintain their consumers' purchasing power. This study aims to determine the marketing communication strategy used by the coffee shop hallo burjois to maintain the purchasing power of its consumers. The subjects in this study were one of the coffee shops located in Karawang and consisted of 4 informants. The data collection techniques used were observation, interviews and documentation. The results of the study showed that the results of the study can show that the marketing communication strategy is very effective and important for coffee shops in maintaining consumer purchasing power at the coffee shop hallo burjois in the midst of the hustle and bustle and tight competition in Karawang. Some of the strategies that were successfully identified include 4p and which were expressed by the owner of the coffee shop hallo burjois himself that they build relationships with customers, one of which is through the use of social media, then hallo burjois also often collaborates to hold activities such as collaborating with communities.